Problem from a Theorem

If \(p\) is an odd prime number, then prove that \( \left( \left( \dfrac{p-1}{2} \right)! \right)^2 + (-1)^\frac{p-1}{2}\) is divisible by \(p\).

Note by Fahim Shahriar Shakkhor
3 years, 11 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

From Wilson's Theorem, \((p-1)! \equiv -1 (\mod p)\)

\(\Rightarrow 1\times2\times........\times \frac{p-1}{2}\times\frac{p+1}{2} \times ..........\times (p-2)\times (p-1) \equiv -1 (\mod p) \)

\(\Rightarrow 1\times2\times........\times \frac{p-1}{2}\times(-\frac{p-1}{2}) \times ..........\times (-2)\times (-1) \equiv -1 (\mod p) \)

\(\Rightarrow ((\frac{p-1}{2})!)^2 \times (-1)^{\frac{p-1}{2}} \equiv -1 (\mod p) \)

\(\Rightarrow ((\frac{p-1}{2})!)^2 \equiv (-1)\times(-1)^{\frac{p-1}{2}} (\mod p)\)

\(\Rightarrow ((\frac{p-1}{2})!)^2 + (-1)^{\frac{p-1}{2}} \equiv 0 (\mod p) \)

Fahim Shahriar Shakkhor - 3 years, 11 months ago

Log in to reply

Nice and tricky!

For convenience, we let \(p=2n+1\) and so we wanna prove that \((n!)^2=n!\cdot n!\equiv (-1)^{n+1}\pmod p\). Now note that \(n\equiv n-p=-(p-n)\pmod p\). So

\[n!=\prod_{k=1}^n k \equiv \prod_{k=1}^n -(p-k)=(-1)^n \prod_{k=1}^n (p-k)=(-1)^n \prod_{k=1}^n (2n+1-k)=(-1)^n \prod_{k=n+1}^{2n} k\pmod p.\]

And hence we have

\[n!\cdot n! \equiv n!\cdot (-1)^n \prod_{k=n+1}^{2n} k=(-1)^n\cdot (2n)!=(-1)^n\cdot (p-1)!\equiv (-1)^n\cdot (-1)=(-1)^{n+1}\pmod p\]

and the last congruence step follows by Wilson's theorem.

Jubayer Nirjhor - 3 years, 11 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...